Evaluation of Hygienic Status and Marketing System of Raw Cow Milk in Different Critical Points of Oromia Special Zone (Global Journal of Science Frontier Research, 2015)
The study was conducted at peri-Addis Ababa districts of Oromia with the aim of assessing hygienic status, knowledge gap, constraints affecting production, marketing and consumption of milk. A total of 102 milk producing farmers at Holeta, Sebeta and Sululta districts, Informal merchant, collection centers dairy cooperative and retail centers at Addis Ababa were engaged by using multi-stage purposive sampling method. About 99% of participants in the areas market whole milk and 94% of the milk produced per households was sold. About 96.1 and 23% of the participants stated that milk production and marketing in areas maintain household food security and profitable farm activity respectively. The major challenges of milk production and marketing in the areas were; feed shortage, high feed cost, disease, shortage of land for grazing, and price fluctuation during fasting season, long term contract for milk marketing and milk quality, respectively.
Keywords: hygienic practice; food security; value chain; critical points; raw milk; knowledge gap